Significance of liver stiffness measurement by acoustic radiation force impulse (ARFI) among hepatitis C patients. Issue 2 (5th November 2013) - Yamada, Ryoko; Hiramatsu, Naoki; Oze, Tsugiko; Morishita, Naoki; Harada, Naoki; Miyazaki, Masanori; Yakushijin, Takayuki; Miyagi, Takuya; Yoshida, Yuichi; Tatsumi, Tomohide; Kanto, Tatsuya; Hayashi, Norio; et al.
<x xml:space="preserve">Abstract</x> The degree of liver fibrosis is strongly associated with the antiviral effect of interferon on chronic hepatitis C patients. In this study, the accuracy of acoustic radiation force impulse (ARFI) in assessing liver fibrosis and the association between liver stiffness using ARFI and antiviral effects were investigated. The 124 patients with chronic hepatitis C enrolled in this study included 94 with HCV genotype 1 and 40 (30%) with moderate fibrosis (METAVIR fibrosis score ≥ F2). Sixty‐one patients received pegylated interferon (peg‐IFN) plus ribavirin combination therapy and the treatment responses were assessed. The shear wave velocity (Vs value) by ARFI had a strong correlation with the histological fibrosis stage (P < 0.001). The AUROC of the Vs value, aspartate aminotransferase platelet ratio index and FIB4 for the diagnoses of moderate fibrosis (≥F2) were 0.890, 0.779, and 0.737, respectively. HCV genotype 1 patients with the TT allele of IL28B and with a low Vs value (<1.40 m/sec) who were treated with peg‐IFN plus ribavirin therapy achieved a sustained virologic response at a rate of 79% (15/19), while all patients with the TG/GG allele of IL28B and a high Vs value (≥1.40 m/sec) experienced a non‐virologic response (6/6). The Vs value measured by ARFI could not predict the treatment response for patients with HCV genotype 2. It is concluded that the combination of ARFI at cut off of 1.4 m/sec and IL28B may be useful for patients with chronic hepatitis C with genotype 1 treated with peg‐IFN/ribavirin combination therapy. J. Med. Virol. 86:241–247, 2014. © 2013 Wiley Periodicals, Inc.